2017
DOI: 10.1016/j.neo.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Human Lymphoproliferative Tumor Formation in Ovarian Cancer Patient-Derived Xenografts

Abstract: Interest in preclinical drug development for ovarian cancer has stimulated development of patient-derived xenograft (PDX) or tumorgraft models. However, the unintended formation of human lymphoma in severe combined immunodeficiency (SCID) mice from Epstein-Barr virus (EBV)–infected human lymphocytes can be problematic. In this study, we have characterized ovarian cancer PDXs which developed human lymphomas and explore methods to suppress lymphoproliferative growth. Fresh human ovarian tumors from 568 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 26 publications
3
56
1
Order By: Relevance
“…D). These results suggest the development of lymphomas in the xenografts as has been reported in PDX studies of various cancers . These three PDX tumors stained positive for the human B‐cell marker CD20 (Fig.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…D). These results suggest the development of lymphomas in the xenografts as has been reported in PDX studies of various cancers . These three PDX tumors stained positive for the human B‐cell marker CD20 (Fig.…”
Section: Resultssupporting
confidence: 78%
“…The histologic appearance of lymphocytes, strong positivity for the human B‐cell marker CD20, transcriptional up‐regulation of immune cell signatures, loss of expression of the HCC‐specific somatic mutations, and distinct CNA profiles suggest that human B‐cell lymphomas were formed in these PDX models. This phenomenon has been described for PDX models derived from a number of human cancer tissues . It has been reported that treatment with rituximab, an anti‐CD20 monoclonal antibody, prevented lymphomatous outgrowth in early passage ovarian xenografts .…”
Section: Discussionmentioning
confidence: 64%
“…2,33 The proliferation of EBV-positive B cells in tumor samples also has been reported to result in the formation of human B-cell lymphomas and the failure of PDX growth in specimens from patients with several types of cancer, including lung cancer. 35 In addition to lymphoma, immune cells present within tumor samples and cotransplanted into the subcutis of NSG mice can induce graft-versushost disease before successful primary tumor engraftment, 30 or coexist with tumor cells in early passages of PDXs. 35 In addition to lymphoma, immune cells present within tumor samples and cotransplanted into the subcutis of NSG mice can induce graft-versushost disease before successful primary tumor engraftment, 30 or coexist with tumor cells in early passages of PDXs.…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, mouse stromal cells in the TME share common features with matched human cells in parental tumors, but the exact impact of murine stroma on human cancer cells in PDX models remains unknown. Third, the engraftment of a PDX can cause lymphoma but not the expected tumors in host mice if the donor patient has a history of Epstein Barr virus infection …”
Section: Introductionmentioning
confidence: 99%